Diseño y aplicación de un Índice de Calidad de Vida en áreas urbanas: el caso de la Cuenca Matanza Riachuelo - Henry, María Laura (2020)
This article aims to expose the design of a Quality of Life Index (QLI) adapted to the socio-environmental reality of the Matanza Riachuelo Basin (located in Argentina), describe its main methodological aspects and show the results obtained from its application in the year 2016, as well as its potential practical uses. The text describes the steps taken to develop the QLI: socio-environmental analysis of the basin, extensive examination of the existing bibliography, elaboration of a conceptual framework to specify the quality of life for the basin, definition and selection of the dimensions and indicators included in the ICV, and, finally, the mapping process through a Geographic Information System (GIS). The results show the existence of significant heterogeneities in the territory under study. It also demonstrates that the intrinsic characteristics of the basin are a significant factor in order to understand the distribution pattern of the QLI, which shows the importance of taking the basins as units of analysis and of administration.